ANALISIS PENDAPATAN WANITA TANI PADI SAWAH MENGGUNAKAN METODE JAJAR LEGOWO DI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Rezki Putra; Evy Maharani; Yulia Andriani (Fakultas Pertanian, Universitas Riau, 2020)
This research aims to analyze the income women rice farmers use jajar legowo method in Empat Balai village and it's efficiency. The research was conducted in Empat Balai village of Kuok district Kampar regency. Sampling was done deliberately (purposive sampling) that women farmers are using jajar legowo method with the total sample as many as 71 women farmers. The results showed the total fixed cost (TFC) for 71 respondents amounted to Rp 37.289.017 planting season with an average of Rp 525,197 planting season, while the total variable cost (TVC) was Rp 102.142.164 planting season or with average variable cost amounting to Rp 1.703.964 planting seasons for each respondent and total cost (TC) production effort women farmers rice method using jajar legowo method in Empat Balai village was Rp 139,431,169 mt, with an average of Rp 1,963,819 mt. Amount of income received women rice farmers using the jajar legowo method was Rp 255,272,331 mt, with an average of Rp 3.595385 mt. And the value of R/C ratio business women farmers rice method using jajar legowo in Empat Balai village was 1.83 > R/C or 1 with an average R/C ratio of 3.56 and the average R/C ratio of the smallest 106, meaning farming is done efficiently